Pembangunan Pedesaan Berbasis Pertanian di Desa Ganra Kecamatan Ganra Kabupaten Soppeng - Wahyuni; Junaeda, St. (Research Agency for Humanity and Urban, 2023)
This study aims to determine the process of implementing agricultural modernization in farming communities and its impact on the socio-cultural life of farmers. The method used is qualitative, namely research conducted with data collection techniques through observation, interviews, and documentation. The results showed that previously farmers in Ganra Village carried out the process of implementing agricultural modernization starting from cultivating paddy fields to processing paddy into rice, initially the tools used in agriculture were still very traditional until they experienced increasingly sophisticated or modern changes. One of them is the inclusion of a combine car during the rice harvest which immediately removes the grain from the stalks or stems and cleaning the grain no longer needs to work twice and even only requires a few people to implement it. Agricultural modernization has positive and negative impacts. The positive impact is increasing crop production, as well as facilitating work that can save time and energy. While the negative impact is making farmers less creative because farmers depend on modern agricultural technology products, increasing unemployment, and lack of mutual cooperation in the social field as well as losing a sense of mutual need between each other and the collective attitude that is characteristic of society. farmers in Ganra Village who have changed to an individual attitude.